Equatorial Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This study discusses a number of policy options that could help transform Equatorial Guinea's oil wealth into sustainable improvements in living conditions. The development of Equatorial Guinea's non-oil sector over the coming years will be essential for long-term economic growth and sustainable poverty reduction. Statistical data of GDP by sector, production of principal export commodities, timber, public investment program, consumer price index, consumer price inflation, fiscal indicators, revenue and expenditure of the central government, monetary survey, balance of payments, petroleum sector accounts, and so on were also presented.